Platelet antigens and antibodies. Literature review - N. V. Mineeva; I. I. Krobinets; M. N. Blinov; S. I. Kapustin (Онкогематология, 2014)
Platelet antigens structure, role of platelet antibodies in the pathogenesis of various clinical conditions, characteristic of modern antibodies detection methods are presented in this article.